THE ACCURACY OF ALGORITHMS FOR WLAN INDOOR POSITIONING AND THE STANDARDIZATION OF SIGNAL RECEPTION FOR DIFFERENT MOBILE DEVICES - Grossmann, Uwe; Schauch, Markus; Hakobyan, Syuzanna (International Journal of Computing, 2014)
Often mobile devices like mobile phones or personal digital assistants (PDA) are equipped with IEEE 802.11 WLAN adapters. Furthermore, within many buildings a WLAN infrastructure is available. The aim of this work is to investigate the quality of different indoor positioning methods based on values of WLAN received signal strength index (RSSI) using commercially available devices (mobile phones, PDA). Three positioning algorithms were considered: minimal Euclidian distance, intersections of RSSI-Isolines and a stochastic model based on Bayes’ theorem. Two measuring testbeds, a museum’s exhibition room and an empty seminar room, four different types of PDA (Dell, Fujitsu, HP, T-Mobile) and two types of access points (Netgear, Lancom) were used. Results show that positioning can be achieved with an average accuracy of approx. 2-3 metres. WLAN capable mobile devices behave differently in receiving RSSI values of a base station. For reasons of standardization a linear correlation between different receiving levels of PDA was investigated.